2019
DOI: 10.1021/acs.joc.9b01253
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition of Lipid II by Lantibiotics: Synthesis and Conformational Studies of Analogues of Nisin and Mutacin Rings A and B

Abstract: In response to the growing threat posed by antibiotic-resistant bacterial strains, extensive research is currently focused on developing antimicrobial agents that target lipid II, a vital precursor in the biosynthesis of bacterial cell walls. The lantibiotic nisin and related peptides display unique and highly selective binding to lipid II. A key feature of the nisin–lipid II interaction is the formation of a cage-like complex between the pyrophosphate moiety of lipid II and the two thioether-bridged rings, ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 142 publications
(123 reference statements)
0
30
0
Order By: Relevance
“…Previously, we have reported the synthesis and average solution phase conformations (calculated in XPLOR‐NIH) of the individual lipid II‐binding rings of nisin and mutacin I . We therefore sought to compare the NAMFIS solutions to these previously calculated structures to determine whether the presence of a second ring significantly affects conformation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we have reported the synthesis and average solution phase conformations (calculated in XPLOR‐NIH) of the individual lipid II‐binding rings of nisin and mutacin I . We therefore sought to compare the NAMFIS solutions to these previously calculated structures to determine whether the presence of a second ring significantly affects conformation.…”
Section: Resultsmentioning
confidence: 99%
“…Another factor to consider,e specially in the interesto fd evelopingm ore stable antibiotics based on the structureo f nisin, [28][29][30][31] is the effect of residue mutation within lantibiotic binding rings on either solutionc onformation or antibacterial activity.S ignificant efforts have been directed towards understanding the effects of dehydro residue replacement,a st hese residues contribute to the metabolic instability of these pep-tides, however no clear picture has yet emerged. Palmer et al have shown that substitution of Dha5 for Ala in nisin ring A leads to significant conformational change of the isolated ring A, [32] conversely,o ur NMR studies [25] comparingi solated ring A structures of nisina nd mutacin Iw ith saturated analogues of mutacin Ir ing Ai ndicated that the replacement of Dha5 by either Ser or Ala did not significantly affectt he overall conformation of the Leu4-Xaa5-Leu6 portion of ring A. This is supported by mutation studies.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations